Were Mankiw, Romer, and Weil Right? A reconciliation of the Micro and Macro Effects of Schooling on Income. (2011)
The marginal product of human capital in Mankiw, Romer, and Weil’s [1992] augmented Solow model measures the direct and two external effects of human capital created from schooling on national income. If this model is valid, its estimates of the share of this marginal product accruing to workers should be consistent with estimates of the marginal return on investment in schooling in workers’ earnings’ studies. This paper uses a new set of data for the net human capital stock to show that in 1990 the micro and macro rates are consistent across 36 countries.